Effects of stocking density on the growth and survival of Oreochromis niloticus cultured in hapas in a concrete tank (African Journal of Fisheries Science, 2022)
The study was conducted over a 90 day period to investigate the effects of stocking density on the growth and survival of fry Oreochromis niloticus cultured in hapas in a concrete tank. Fish of average initial weight 0.3 g ± 0.03 were stocked at three different rates: 8, 10 and 12 fish/m3 corresponding to 56, 70 and 84 fish per hapa. Fish were fed twice daily with powdered pito mash at 10% of the biomass. The average initial weights of the fish varied slightly but not significant (P > 0.05) among all the treatments. At the end of the trial, the average final weights varied significantly (P < 0.05). Fish stocked at 8 m3 exhibited the highest average weight gain (4.65 ± 0.19 g) whiles; fish stocked at 12 m3 recorded the lowest average weight gain (2.50 ± 0.27 g). Feed conversion ratio and specific growth rate were not significantly different (P > 0.05) for all treatments. Survival rate were similar (P > 0.05) among treatments. The results demonstrate that increasing rearing density in fry O. niloticus resulted in heterogeneous growth rates. Feed conversion ratios, specific growth and survival rates were not affected by different stocking densities.